The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/09553002.2017.1397296
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents possible radiotherapy-induced thyroid injury

Abstract: Melatonin helped protect thyroid gland structure against the undesired cytotoxic effects of radiotherapy in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Melatonin coadministration to hyperthyroid rats significantly improved the architecture of the thyroid tissue, as shown by the presence of the majority of thyroid follicles with a regular structure and homogenous colloids. The present observations concerning melatonin are somewhat similar to those from earlier studies, which suggested that melatonin has a protective effect against thyroid gland injury (Arıcıgil et al, 2017). The histopathological analysis conducted on the thymus gland revealed that hyperthyroidism caused significant degenerative modifications, notably apoptotic lymphocytes and dispersed necrotic changes in the medullary area.…”
Section: Discussionsupporting
confidence: 91%
“…Melatonin coadministration to hyperthyroid rats significantly improved the architecture of the thyroid tissue, as shown by the presence of the majority of thyroid follicles with a regular structure and homogenous colloids. The present observations concerning melatonin are somewhat similar to those from earlier studies, which suggested that melatonin has a protective effect against thyroid gland injury (Arıcıgil et al, 2017). The histopathological analysis conducted on the thymus gland revealed that hyperthyroidism caused significant degenerative modifications, notably apoptotic lymphocytes and dispersed necrotic changes in the medullary area.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that melatonin is able to neutralize different types of free radicals directly or via activation of antioxidant enzymes such as superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPx), catalase (CAT), and glutathione reductase (GR) (25). Several bodies of evidence have suggested that melatonin inhibits reduction/oxidation reactions following exposure to radiation, leading to inhibition of chronic oxidative stress in irradiated cells (26). A systematic review by Zetner and colleagues proposed that melatonin can be potentially used for cancer patients undergoing radiotherapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…SW therapy mechanisms of various diseases have been published, including increase of anti-inflammation [ 17 , 18 , 20 , 43 , 44 ] and anti-oxidative stress [ 17 , 18 , 20 , 45 ]. The mechanisms of Mel therapy in various diseases have also been published, including increase of anti-oxidative stress [ 15 , 46 , 47 , 48 , 49 , 50 ] and anti-inflammation [ 50 , 51 , 52 , 53 ]. Based on our findings, the proposed mechanisms of Mel combined SW therapy on DN are summarized in Figure 8 .…”
Section: Discussionmentioning
confidence: 99%